Agronomic Bio-fortification of Zinc in Indigenous, High Yielding and Hybrid Rice (Oryza sativa L.) Cultivars - and Rajon Kumar Ojha, Arvind Kumar, Manas Denre, B.K. Agarwal, Manish Kumar (Journal of the Indian Society of Soil Science, 2016)
Field experiment was conducted to assess the Zn content of rice grain and straw with and without Zn fertilizer application in a red and lateritic soil of Ranchi (Jharkhand). While, the grain yield of hybrid rice was considerably higher as compared to high yielding and indigenous rice cultivars, the response to added Zn in rice was not significant. Highest content of Zn (37.1 mg kg-1) was recorded in rice grain of indigenous rice cultivars, when Zn was applied @ 100 kg ha-1 of ZnSO4.7H2O (soil application) + 3 foliar application of 0.5% ZnSO4.7H2O. Results suggested that indigenous and high yielding rice cultivars were more suited than hybrids in red and lateritic soil for agronomic bio-fortification. Content of Zn in rice grain of indigenous cultivars was higher (32.1 mg kg-1) followed by HYV (26.7 mg kg-1) and hybrid (24.1 mg kg-1) cultivars of rice. Total Zn removal by rice crop was 0.44, 0.65 and 0.63 kg ha-1, respectively when indigenous; HYV and hybrid rice cultivars were grown without any addition of Zn. Soil as well as soil + foliar application of Zn increased the Zn uptake by rice more than two times, compared to its non-application. Apparent Zn recovery in rice was low i.e. 1.99, 1.49 and 1.08 per cent only with soil application of 100 kg ha-1 of ZnSO4.7H2O, respectively by hybrid, HYV and indigenous rice cultivars. This was considerably higher i.e. 4.32% in hybrid, 3.19% in HYV and 2.53% in indigenous rice cultivars, when Zn was added through soil (100 kg ha-1 of ZnSO4.7H2O) + foliar application of 0.5% ZnSO4.7H2O.